Social capital, local actor networks and differential economic performance in rural areas - evidence from case studies in Germany - Helmut Schrader (European Regional Science Association (ERSA), 2002)
The changing economic and social conditions of rural areas in Europe are characterised by variety of different development processes. An EU-funded international research project which has been conducted in collaboration with Scottish, Swedish, German and Greek research institutes focussed on the dynamics of rural areas (DORA). The research approach aimed to examine the quantitative and qualitative factors explaining the differences of economic performance (DEP) in selected rural regions of the four member states involved. Important variables of the investigation are the infrastructure equipment, the regional economic structure, the employment conditions and other socio-economic data as well as qualitative variables such as social capital in combination with local actor networks and institutional collaboration at the regional level. In this paper the role of social capital will be determined in quantitative and qualitative terms and in relation to other "soft" factors of rural development. The approach is characterised by a number of pair-wise comparisons of differing rural areas in terms of economic performance and based on exemplary results from the European Union research project DORA. After explaining the case study approach and clarifying the definition of social capital an operational conception of indicators for measuring of social capital will be presented with regard to regional-economic analysis. Statistical methods of locational conditions and differences of the socio-economic context are considered. Furthermore, expert interviews with regional actors as well as findings derived from postal business surveys serve as information bases for the analysis. The impact of social capital on regional institutions, politics processes and the differences of the economic dynamics is considered in each pair of case studies of the two examined regions in West and East Germany. From the comparison of the two regions the conclusion is derived that the regional differences regarding the amount and quality of social capital can contribute considerably to the explanation of differing development paths under similar context conditions and that the role of social capital could be more strongly taken into account with regard to impact assessment of regional policy.
Keywords: 330